Frontline yet at the back of the queue – improving access and adaptations to CBT for Black African and Caribbean communities. (19th October 2021) - Lawton, Leila; McRae, Melissa; Gordon, Lorraine
Abstract: This paper focuses on the Black minority ethnic population (Black British, Black African, Black Caribbean) and uses the term BME in reference to this group. Only 6.2% of BME people access psychological intervention for common mental disorders. In provision of cognitive behavioural therapy (CBT) the diversity in global majority populations 1 requires culturally specific informed and responsive approaches. The Improving Access to Psychological Therapies (IAPT) programme needs to be accountable, culturally congruent and strategic, to ensure accessibility and improve outcomes for BME people. According to the Mental Health Foundation (2019), a higher percentage of Black, Asian and other minority ethnic populations (BAME) are diagnosed with common, severe and complex mental health disorders. Despite the weight of literature on this, little has changed. The NHS Implementation Plan outlines trajectories for increased access and reduced attrition within mental health services, addressing inequalities for BAME populations. Evidence-based guidance and audits for provision of culturally sensitive and adapted therapies are presented in the pioneering (IAPT) BAME Positive Practice Guide (PPG). However, there are no funding arrangements or formal integrated frameworks to support implementation. The COVID-19 global pandemic and the high-profile death of George Floyd tragically exposed and highlighted the consequences of systemic racism. Understanding of the importance of service and clinical anti-racist practice is imperative for CBT therapists. Implementation of the BAME PPG audit tool ensures review of race equity in access, engagement, adaptation and workforce within IAPT and other mental health services. This could transform lives. Key learning aims: (1) To understand the barriers (individual, societal and systemic) to accessing psychological therapies such as CBT and the impact on CBT treatment outcomes specifically for black minority ethnic (BME) populations. (2) To recognise barriers to implementation of formal frameworks for equitable access to psychological therapies such as CBT for BME communities. (3) To assist services and therapists to implement evidence-based learning, on cultural adaptations, to address barriers in access, retention and completion of CBT. (4) To provide examples of services that have taken successful actions to address the issues identified in the earlier points.